A fear of coercion and accountability?: security officers and the non-use of force - Eski, Yarin (Policing and society, 2018)
Based on fieldwork among operational security officers working in the Hamburg and Rotterdam ports, it became clear these frontline port policing professionals possess a critical, even fearful attitude towards coercion while performing their duties in the ports. The power of arrest and the possibility of being weaponised were especially problematic. Overall, they revealed a rather different attitude towards coercion than is generally ascribed to security officers and accounted for in (critical) criminological literature. This paper will explore the extent to which (the stereotype of) security officers being power hungry and trigger-happy cowboys is a correct reflection of port security occupational realities in Northwest Europe. Empirical evidence is provided on security officers’ worry and fear of using power, weaponisation, and accountability. It will show that the security officers, responsibilised for making port communities feel safer and the port as highly important global critical infrastructure more secure, are fearful and risk-averse themselves. Meaning that, if security officers fear to coerce (with weapons) due to accountability fear, which turns them idle, it implies we are witnessing the delivery of a placebo security that deserves further scrutiny.